Expansion of integrative and complementary practices in brazil and the process of implementation in the single health system - Ferraz, Ivana Santos (2019)
The present study aimed to present a reflection on the expansion of the National Policy of Integrative and Complementary Practices in the Unified Health System in the last 13 years in Brazil. health services and the implication of the authors themselves in this experience. This is an integrative review with analysis of academic production in the last 13 years (2006 to 2019) searching the database of the Virtual Health Library. We selected 7 papers that comprised the body of this study. Given the reflections presented in this study, it is possible to observe, over the last 13 years, the presence of the expansion of the Integrative and Complementary Practices, especially in the Northeast and Southeast, being undeniable the positive impact of these practices in Brazil. However, the inclusion of Integrative and Complementary Practices in the Unified Health System constitutes an action to expand access and qualification of services, from the perspective of comprehensive health care for the population. Given the above, it is reaffirmed the need to undertake new academic studies regarding the implementation of the National Policy of Integrative and Complementary Practices in Health in Brazil, with a view to analyzes directed to significant reduction of financial resources, especially by political and economic period that Brazil faces today.